2011
DOI: 10.1007/s00453-011-9533-2
|View full text |Cite
|
Sign up to set email alerts
|

An Exact Exponential Time Algorithm for Power Dominating Set

Abstract: The POWER DOMINATING SET problem is an extension of the well-known domination problem on graphs in a way that we enrich it by a second propagation rule: given a graph G(V , E), a set P ⊆ V is a power dominating set if every vertex is observed after the exhaustive application of the following two rules. First, a vertex is observed if v ∈ P or it has a neighbor in P . Secondly, if an observed vertex has exactly one unobserved neighbor u, then also u will be observed, as well. We show that POWER DOMINATING SET re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Liao and Lee [10] showed a different NP-completeness proof for the PDS problem in split graphs as well as introduced a polynomial-time algorithm for solving PDS optimally on interval graphs. As shown by Binkele-Raible and Fernau, the PDS problem continues to be NP-hard on cubic graphs [11]. Guo et al [6] also presented valid orientations to optimally address PDS on undirected graphs having bounded tree-width.…”
Section: Power Domination and Related Workmentioning
confidence: 99%
“…Liao and Lee [10] showed a different NP-completeness proof for the PDS problem in split graphs as well as introduced a polynomial-time algorithm for solving PDS optimally on interval graphs. As shown by Binkele-Raible and Fernau, the PDS problem continues to be NP-hard on cubic graphs [11]. Guo et al [6] also presented valid orientations to optimally address PDS on undirected graphs having bounded tree-width.…”
Section: Power Domination and Related Workmentioning
confidence: 99%
“…Current research on the PDSP mostly focuses on its theoretical aspects. It has been shown that the PDSP is NP‐hard even on specific types of graphs like cubic graphs (Binkele‐Raible & Fernau, 2012). Another direction of research has been in finding the optimal size or bounds for specific graphs like grid graphs (Dorfling & Henning, 2006; Pai, Chang, & Wang, 2007), hyper cubes (Dean, Ilic, Ramirez, Shen, & Tian, 2011), generalised Petersen graphs (Koh & Soh, 2016; Lai, Chien, Chou, & Kao, 2012), cylinders (Koh & Soh, 2016), circular‐arc graphs (Liao & Lee, 2013), and tori (Koh & Soh, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Only a small amount of published research is dedicated to solving the PDSP on general graphs. In (Binkele‐Raible & Fernau, 2012; Raible & Fernau, 2008) a method based on reference search trees is developed for finding optimal solutions having a computational complexity of scriptO()1.7548n. Optimal solutions for the PDSP and the CPDSP have also been found using integer linear programs (ILP; Brimkov et al, 2017; Fan & Watson, 2012; Aazami & Stilp, 2009).…”
Section: Introductionmentioning
confidence: 99%